Interstitial laser anterior capsulotomy for obsessive–compulsive disorder: lesion size and tractography correlate with outcome. Issue 3 (29th October 2021) - Satzer, David; Mahavadi, Anil; Lacy, Maureen; Grant, Jon E; Warnke, Peter
Abstract : Background: Anterior capsulotomy is a well-established treatment for refractory obsessive–compulsive disorder (OCD). MRI-guided laser interstitial thermal therapy (LITT) allows creation of large, sharply demarcated lesions with the safeguard of real-time imaging. Objective: To characterise the outcomes of laser anterior capsulotomy, including radiographical predictors of improvement. Methods: Patients with severe OCD refractory to pharmacotherapy and cognitive–behavioural therapy underwent bilateral anterior capsulotomy via LITT. The primary outcome was per cent reduction in Yale-Brown Obsessive–Compulsive Scale (Y-BOCS) score over time. Lesion size was measured on postablation MRI. Disconnection of the anterior limb of the internal capsule (ALIC) was assessed via individual and normative tractography. Results: Eighteen patients underwent laser anterior capsulotomy. Median follow-up was 6 months (range 3–51 months). Time occupied by obsessions improved immediately (median Y-BOCS item 1 score 4–1, p=0.002). Mean (±SD) decrease in Y-BOCS score at last follow-up was 46%±32% (16±11 points, p<0.0001). Sixty-one per cent of patients were responders. Seven patients (39%) exhibited transient postoperative apathy. One patient had an asymptomatic intracerebral haemorrhage. Reduction in Y-BOCS score was positively associated with ablation volume (p=0.006). Individual tractography demonstrated durable ALIC disconnection. Normative tractography revealed a dorsal–ventral gradient, with disconnection of orbitofrontal streamlines most strongly associated with a positive response (p<0.0001). Conclusions: Laser anterior capsulotomy resulted in immediate, marked improvement in OCD symptom severity. Larger lesions permit greater disconnection of prefrontal–subcortical pathways involved in OCD. The importance of greater disconnection is presumably related to variation in ALIC structure and the complex role of the PFC in OCD.